Cointegration and causality in capital markets - Ahmet Can Inci (Journal of Capital Markets Studies (JCMS), 2018)
Purpose - The purpose of this paper is to study the efficiency of different oil and gas markets. Most previous studies examined the issue using low frequency date sampled at monthly, weekly, or daily frequencies. In this study, 30-minute intraday data are used to explore efficiency in energy markets. Design/methodology/approach - Sophisticated statistical analysis techniques such as Granger-causality regressions, augmented Dickey-Fuller tests, cointegration tests, vector autoregressions are used to explore the transmission of information between oil and gas energy markets. Findings - This study provides evidence for efficiency in energy markets. The new information that arrives either to futures markets or spot markets is digested correctly, completely, and in a fast manner, and is propagated to the other market. The evidence indicates high efficiency. Originality/value - This study is one of the first papers that uses 30-minute interval intraday data to investigate efficiency in oil and gas commodity markets.
Keywords: G13; G14; Q32; Q35; Q41; 330; Cointegration; Energy; Commodity markets; Oil and gas markets